(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article reveals the history of the formation of the Samarkand Agricultural Institute and the periods of its development in the first half of the ХХ century. In addition, archival materials related to the history of the institute, reports of the faculties and departments of the institute, as well as private memoirs were analyzed. When covering the topic, special attention was paid to revealing the features of the educational system of the Institute, determining its place in the education system of the region and its contribution to the national economy, showing the activities of scientific schools in the history of the Institute, the stages of development of the Institute and their factors.